Enhancing teaching and learning in schools through instructional leadership: South African perspective - Aphane, Venessa; Agyeman, Nana Yaw Brenya (STAI Auliaurrasyidin Tembilahan, 2025)
This qualitative case study examines instructional leadership's role in enhancing education quality in South African schools, where persistent learner underperformance reflects systemic challenges. Despite the Department of Basic Education’s reports highlighting widespread underperformance, limited research explores how school leaders address these issues. Focusing on a public secondary school, the study purposively sampled eight school leaders, employing semi-structured interviews to gather data. Thematic analysis revealed that effective instructional leadership strengthens curriculum alignment and resource allocation, with principals serving as pivotal actors. However, gaps persist in leadership practices, necessitating targeted improvements. Key strategies include adopting learner-centered pedagogies, fostering teacher autonomy, and cultivating supportive learning environments. The findings underscore the urgency of prioritizing instructional leadership to mitigate systemic inefficiencies and improve knowledge acquisition. This study contributes to the discourse on educational leadership in low-performing contexts, advocating for policy and practice reforms to address South Africa’s declining education outcomes.